Implementasi “The Flash” New Character Building Dalam Upaya Meningkatkan Revolusi Mental Karyawan PT. Swabina Gatra - Amelia, Nabila; Prianggi Amelasasih (Lembaga Pengembangan Kinerja Dosen, 2024)
In the current global era, character building is needed in all fields, especially in companies that want their human resources to be better at work.